Impact of Social Media Marketing Activities on Consumer Preferences for Kitchen Tools and Equipment - Ahmed, Wafa Hamid Abdelrahman Mohamed (Journal of Ubiquitous Computing and Communication Technologies, 2025)
It also states the growing influence of Social Media Marketing Activities (SMMAs) on the buying behavior of customers in the kitchen equipment and tools industry. With more customers making online purchases, marketing activities have to be re-engineered in a bid to keep abreast of changing demands. This exploratory case study conducted a survey of 214 consumers to analyze the impact of five dimensions of social media marketing activities (SMMAs), namely entertainment, interactivity, trendiness, electronic word-of-mouth (e-WOM), and customization, on consumer engagement, trust, and kitchen tools and equipment selection. Embedded in the Elaboration Likelihood Model (ELM), Social Presence Theory, and the Theory of Planned Behavior (TPB), this study develops and tests a conceptual model linking SMMAs to phases of the consumer decision process. Results show that effective utilization of SMMAs reinforces brand awareness, loyalty, and positive consumption behavior. The study contributes by extending theories of persuasion and engagement to the kitchenware sector and offering practical recommendations for marketers operating on social networking websites within competitive consumer markets.
Keywords: Social Media Marketing Activities (SMMA); Consumer Preferences; Purchase Decision; Kitchen Tools; Kitchen Equipment